Preparation method and application of trioxytriphenylamine covalent organic framework with near-infrared photothermal catalysis Suzuki reaction performance

The trioxytrianilin-based covalent organic framework (TANG-NDI COFs) prepared by using donor (D)-acceptor (A) copolymerization strategy in photothermal catalysts is used to achieve efficient photothermal conversion using near-infrared LED lamps, solving the problems of high cost and limited application scope of traditional photocatalytic technology, and achieving efficient and economical photothermal catalytic effect.

CN119875121APending Publication Date: 2025-04-25DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510085093.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional photocatalytic technology has problems such as high cost, limited scope of application, and many side reactions. The band gap of existing photothermal catalysts is large, which affects the photothermal conversion efficiency.

Method used

The donor (D)-acceptor (A) copolymerization strategy was used to prepare trioxytrianilin-based covalent organic framework (TANG-NDI COFs), and efficient photothermal conversion was achieved through the irradiation of near-infrared LED lamps, which promoted electron transfer between the catalyst and the substrate.

Benefits of technology

Near infrared photothermal catalytic Suzuki reaction was achieved, with a yield of more than 80%, saving 40% of the heat source cost, the catalyst can be recycled, and the cyclic catalytic efficiency has not decreased significantly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875121A_ABST
    Figure CN119875121A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photo-thermal catalytic materials, and relates to a preparation method and application of a trioxytriphenylamine covalent organic framework with near-infrared photo-thermal catalysis Suzuki reaction performance, and the preparation method comprises the following steps: taking triamino trioxytriphenylamine NH2-TANG as an organic ligand, taking naphthalimide NDI as a linking group, and carrying out a solvothermal method to prepare the trioxytriphenylamine covalent organic framework with near-infrared photo-thermal catalysis Suzuki reaction. The trioxytriphenylamine covalent organic framework TANG-NDI COFs with the near-infrared photothermal catalysis Suzuki reaction performance is prepared, and the synthesis route of the trioxytriphenylamine covalent organic framework TANG-NDI COFs is NH2-TANG + NDI-TANG-NDI COFs. The trioxytriphenylamine covalent organic framework TANG-NDI COFs prepared by the method disclosed by the invention can catalyze the Suzuki reaction of chlorides under the irradiation of a near-infrared LED (Light Emitting Diode) with the wavelength of 650-850 nm, so that the Suzuki reaction yield of the chlorides is almost the same as that of bromides and iodates, the yield is 80% or above, the heat source cost is saved by 40%, and the catalyst can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a trioxytriphenylamine-based covalent organic framework with near-infrared photothermal catalytic Suzuki reaction performance, belonging to the technical field of photothermal catalytic materials. Background Art

[0002] Traditional photocatalytic technology mainly relies on the single electron transfer (SET) mechanism, usually using blue-violet light as the light source. However, due to the high energy and low penetration of blue-violet light, traditional photocatalytic technology is difficult to be applied on a large scale in the industrial field. During the reaction process, a large amount of electron donors, such as triethylamine, DIPEA, etc., usually need to be added, which undoubtedly greatly increases the cost of the reaction. At the same time, the scope of application of traditional photocatalysts is very limited, and is usually only applicable to a few specific types of reactions, which undoubtedly poses an obstacle to the industrialization of photocatalytic technology.

[0003] Compared with traditional photocatalytic technology, photothermal catalytic technology has the advantages of wider application range, lower cost, longer light source wavelength and fewer side reactions, which facilitates the promotion of photothermal catalytic technology in large-scale industrial applications. At present, photothermal catalysts can be divided into three categories: metal nanomaterials, metal-loaded carbon-based semiconductor materials and conjugated polymer materials. The development of the first two photothermal materials is relatively mature, but there are certain disadvantages. For example, the use of metal catalysts may cause the inactivation of certain macromolecular proteins, so it is not suitable for biological science related fields; in cases where other metals need to be introduced to catalyze organic reactions, metal-based catalysts may interfere with the reaction process, resulting in reduced reaction yields and increased side reactions, especially when synthesizing compounds of specific configurations and conformations. The introduction of other metals may cause experimental failures; in the field of drug synthesis, the use of metal-based catalysts may cause metal residues, especially metal-loaded catalysts, which are usually connected in a coordinated manner, and are more likely to have residual metals, making it difficult to ensure the safety of drugs. Metal-free conjugated polymer materials have inherent advantages over the former. When the photon energy is close to the electron transition energy within the molecule, the electron will be excited from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). After the transition, the electrons in the lowest unoccupied molecular orbital return to the ground state through the electron-phonon coupled thermal relaxation process. The thermal relaxation process is accompanied by abundant thermal vibration phenomena, which manifests itself macroscopically as an increase in the temperature of the material. However, conjugated polymers often have a large band gap. A large band gap means that the material has a larger fluorescence quantum yield, which greatly affects the photothermal conversion efficiency of the material. This also greatly limits its development as a photothermal material, so how to effectively reduce the band gap has become the focus of the development of polymer-based photothermal materials.

[0004] As a type of porous polymer, covalent organic frameworks (COFs) have significant characteristics including extremely high specific surface area, large porosity and strong thermochemical stability. These characteristics make covalent organic frameworks (COFs) more suitable as efficient photocatalysts. The flexibility and controllability of its structure further promote researchers' exploration and application in various photocatalytic reactions. In addition, the low solubility of covalent organic frameworks (COFs) facilitates the recovery and reuse of catalysts, ensuring its economic feasibility in practical applications. Compared with traditional homogeneous catalysts, heterogeneous photocatalyst covalent organic frameworks (COFs) show significant advantages. First, covalent organic frameworks (COFs) have high porosity and large specific surface area, which not only helps to improve catalytic activity, but also promotes the mass transfer process of substrates, greatly improving the yield of catalytic reactions; in covalent organic frameworks (COFs), all chemical bonds are covalent bonds, which gives covalent organic frameworks (COFs) excellent chemical stability and thermal stability. Therefore, in most reaction systems, even in the face of harsh conditions, it can still maintain its structural stability and can be recycled after the reaction; the π...π interaction and infinitely extended conjugated structure of covalent organic frameworks (COFs) not only promote the separation, diffusion and migration of photogenerated electron-hole pairs, but also facilitate efficient photothermal conversion. Therefore, covalent organic frameworks (COFs) are a class of photothermal catalytic materials with great development prospects. However, due to the limited number of π electrons and the presence of a large number of σ bonds in conjugated polymers, their narrow absorption spectrum range and low carrier mobility limit their application in the field of photothermal conversion. In order to overcome this limitation, this study adopted a donor (D)-acceptor (A) copolymerization strategy.

[0005] Donor (D)-acceptor (A) type covalent organic frameworks (COFs) are known for their unique structural properties. Their main chain is composed of donor (D) units and acceptor (A) units arranged alternately, which gives them a special interaction force, namely DA interaction. This strong interaction leads to a red shift in the absorption spectrum of DA-type covalent organic frameworks (COFs), and some materials can even absorb near-infrared light. With the enhancement of DA interaction, the red shift of its absorption band becomes more and more significant. In addition, DA interaction is easy to generate Dirac cones, and low-energy excitation allows electrons to make non-radiative transitions along the Dirac cone, greatly improving the photothermal efficiency and the possibility of industrialization of photothermal materials, which is more conducive to our development of near-infrared photothermal catalysts. Therefore, we prepared covalent organic frameworks (COFs) with strong DA interaction structure: TANG-NDI COFs, which have a wide electron transfer (CT) absorption band of 650nm-850nm under non-illumination.

[0006] The Suzuki-Miyaura coupling reaction (Suzuki reaction for short) is one of the most widely used synthetic methods. The reaction uses organic borides and halides as raw materials, can efficiently construct carbon-carbon bonds, and has outstanding advantages such as mild reaction conditions, efficient conversion and wide substrate universality. It has a wide range of applications in different fields such as fine chemicals, medicines, pesticides and organic materials. The catalytic cycle of the Suzuki reaction is generally divided into three basic steps: (1) zero-valent palladium is inserted into the carbon-halogen bond to form divalent palladium; (2) the nucleophilic group of the organoboron reagent migrates to the palladium; (3) the coupling product and zero-valent palladium are simultaneously generated (zero-valent palladium will then undergo subsequent oxidative addition to complete the next catalytic cycle). However, in the Suzuki reaction, the halides used are mostly bromides and iodides, and the reaction of chlorinated compounds is more difficult, in addition to requiring the use of higher temperatures; sometimes some expensive ligands are added, such as the bidentate ligand bipyridine, but high temperatures will cause the deactivation and decomposition of tetrakis(triphenylphosphine)palladium and many side reactions, and the homogeneous ligand dissolved in the solvent will also become a new impurity, which increases the difficulty of product separation. For the Suzuki reaction of chlorinated compounds, predecessors have developed a series of catalysts that are expensive, harsh and have poor stability, which is undoubtedly not conducive to industrial production. For example, predecessors used special catalysts and high-temperature microwave heating at 140 °C to apply chloroarylphosphine oxides to the Suzuki reaction. Microwave heating is similar to photothermal catalysis, both of which transfer heat at the molecular vibration level. Microwave catalysis requires relatively expensive equipment to react, but photothermal catalysis can only rely on solar energy to react and the photothermal catalyst can be recycled. Therefore, using photothermal catalysis to catalyze the Suzuki reaction of chlorinated compounds without external ligands has become a new development direction. Summary of the invention

[0007] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a preparation method and application of a trioxy triphenylamine-based covalent organic framework having near-infrared photothermal catalytic Suzuki reaction performance. The method of the present invention realizes efficient photothermal conversion by irradiation of a near-infrared LED lamp, so that the catalyst temperature rises sharply, thereby easily crossing the potential barriers of many organic reactions and realizing efficient photothermal catalysis. At the same time, the trioxy triphenylamine-based covalent organic framework obtained by this preparation method can efficiently transfer energy with the substrate in the pores, promoting the electron transfer process between the catalyst and the substrate under light excitation conditions.

[0008] In order to achieve the above-mentioned invention object, the technical scheme adopted by the present invention is: a method for preparing a trioxy triphenylamine-based covalent organic framework having near-infrared photothermal catalytic Suzuki reaction performance, using triamino trioxy triphenylamine NH2-TANG as an organic ligand and naphthalene diimide NDI as a connecting group, through a solvothermal method, to prepare a trioxy triphenylamine-based covalent organic framework TANG-NDI COFs having near-infrared photothermal catalytic Suzuki reaction performance, and the synthesis route is as follows:

[0009] NH2-TANG +NDI→ TANG-NDI COFs;

[0010] The organic ligand NH2-TANG has the following molecular structure formula (A):

[0011]

[0012] The connecting group has the following molecular structure formula (B):

[0013]

[0014] In order to verify the structure of the material later, the corresponding monomer was synthesized with the following molecular structure formula (C):

[0015]

[0016] The preparation method includes the preparation of the target material and the preparation of the monomer, wherein the preparation of the target material includes the following steps:

[0017] Step 1, dissolving a mixture of 25-35 g 2,6-difluoroaniline, 12-21 g 3-fluoro-2-iodoanisole, 52-70 g potassium carbonate, 12-20 g copper powder and 3.2-6 g 18-crown ether-6 in 120-200 ml 1,2-dichlorobenzene, subjecting the mixture to 2-3 vacuum-nitrogen cycles, stirring the mixture at 120-160 ° C for 12-18 hours, filtering out insoluble matter through a Buchner funnel, concentrating the filtrate under reduced pressure, and purifying by silica gel column chromatography to obtain a light yellow powder;

[0018] Step 2, adding the light yellow powder obtained in step 1 to a round-bottom flask, and adding 35-45 g of 2-iodo-1,3-dimethoxybenzene, 2-5 g of 18-crown ether-6, 30-50 g of potassium carbonate, 9-15 g of copper powder and 150-200 ml of mesitylene, and then stirring the mixture at 160-210 ° C for 40-56 hours, filtering out insoluble matter through a Buchner funnel, concentrating the filtrate under reduced pressure, and purifying the crude product by silica gel column chromatography to obtain a white powder;

[0019] Step 3, add the white powder obtained in step 2 to a round-bottom flask, and add 300-350 ml of dry CH2Cl2, cool the system to -78 °C, add 65-80 ml of BBr3 and slowly stir for 6-12 hours to warm to room temperature, then pour the reaction mixture into ice water, extract with ethyl acetate, filter and concentrate under reduced pressure to obtain a demethylated crude product as a white solid, dissolve the white solid in 200-230 ml of DMF, add 15-25 g of potassium carbonate, and stir the mixture at 100-120 °C for 18-24 hours, filter out insoluble matter through a Buchner funnel, concentrate the filtrate under reduced pressure, and purify the crude product by silica gel column chromatography to obtain a light yellow powder;

[0020] Step 4: Slowly add the light yellow powder obtained in step 3 into a round-bottom flask containing 50-75 ml 69-71% HNO3 and placed in an ice bath, then slowly add 12-15 ml (CH3CO)2O and 20-25 ml CH3CO2H, stir the mixture at a constant temperature for 25-45 minutes, then pour the mixture into ice water, filter the precipitate to obtain a dark red powder;

[0021] Step 5, add the dark red powder obtained in step 4 to a round-bottom flask, and add 40-65 ml of dry tetrahydrofuran and 8-10 g of 10% Pd / C catalyst, connect a hydrogen bottle to the outlet of the round-bottom flask, purge the mixture with hydrogen, and react at room temperature for 24-36 hours, then filter out the insoluble matter in a glove box, and evaporate the filtrate to dryness under reduced pressure to obtain a dark green powder, i.e., the organic ligand NH2-TANG;

[0022] Step 6, weighing the organic ligand NH2-TANG and NDI in a molar ratio of 1:1.2~1.5, adding them to a heat-resistant glass tube containing a mixed solvent of m-cresol, methyl pyrrolidone, and isoquinoline in a volume ratio of 1:0.2~0.3:0.005~0.012, and ultrasonically dispersing them uniformly; using liquid nitrogen to freeze the glass tube and flame-seal the tube mouth under vacuum, then placing it in an oven with a temperature control program, heating it to 180~200°C, and maintaining a constant temperature reaction for 100~120 hours; after the reaction is completed and cooled to room temperature, removing the supernatant, adding m-cresol for washing, centrifuging, repeating the operation 2~3 times, collecting the bottom product, and obtaining a black powder, i.e., the target material trioxytriphenylamine-based covalent organic framework TANG-NDI COFs;

[0023] The monomer is prepared by dissolving the organic ligand NH2-TANG and 1,8-naphthalene dicarboxylic anhydride in 35-60 ml of m-cresol at a molar ratio of 1:3-5, reacting at 160-200 °C for 24-36 hours, and then filtering to obtain the monomer as a brown powder.

[0024] The trioxytriphenylamine-based covalent organic framework TANG-NDI COFs prepared by the method is used in the near-infrared photothermal catalytic Suzuki reaction.

[0025] The invention has the beneficial effects of: a preparation method and application of a trioxy triphenylamine-based covalent organic framework with near-infrared photothermal catalytic Suzuki reaction performance, wherein the preparation method is to use triamino trioxy triphenylamine NH2-TANG as an organic ligand and naphthalene diimide NDI as a connecting group, and to prepare the trioxy triphenylamine-based covalent organic framework TANG-NDI COFs with near-infrared photothermal catalytic Suzuki reaction performance through a solvothermal method, and the synthesis route is as follows: NH2-TANG +NDI→ TANG-NDI COFs; the absorption peak of the material is red-shifted to the near-infrared region through the interaction between trioxy triphenylamine TANG and naphthalene diimide NDI, and the band gap of the material is reduced through extensive π...π stacking, which is beneficial to the recombination of electrons and holes, reduces the fluorescence quantum yield, and thus promotes the non-radiative thermal relaxation of electrons. The trioxytriphenylamine-based covalent organic framework TANG-NDI COFs prepared by the method of the present invention can catalyze the Suzuki reaction of chlorinated substances under the irradiation of a near-infrared LED with a wavelength of 650-850 nm, so that the yield of the Suzuki reaction of chlorinated substances is almost the same as that of brominated substances and iodinated substances, and the yield is above 80%, saving 40% of the heat source cost, and the catalyst can be recycled, and the cyclic catalytic efficiency has not decreased significantly, and can still reach more than 80% after five cycles. Not only has the photothermal heating method replaced the traditional heating method, but the light source used is a near-infrared light source with strong penetration. Since most of the sunlight is near-infrared light, sunlight can be used to replace the LED light source, so that photothermal catalysis has the potential for large-scale industrialization and industrialization. The target material TANG-NDI COFs prepared by the present invention has high yield and stable chemical properties, mature preparation technology, and is easy to prepare on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the crystal structure of the target material TANG-NDI COFs in Example 1.

[0027] Figure 2 This is the infrared spectra of the target material TANG-NDI COFs and monomers in Example 2.

[0028] Figure 3 This is the PXRD pattern of the target material TANG-NDI COFs in Example 1.

[0029] Figure 4 This is the thermogravimetric analysis diagram of TANG-NDI COFs, the target material of Example 3.

[0030] Figure 5It is the UV-visible absorption spectra of the target material TANG-NDI COFs and monomers of Example 4.

[0031] Figure 6 It is the electron paramagnetic resonance spectrum of the target material TANG-NDI COFs and monomers in Example 5.

[0032] In the figure: (a) is the electron paramagnetic resonance spectrum of TANG-NDI COFs, and (b) is the electron paramagnetic resonance spectrum of the monomer.

[0033] Figure 7 This is a schematic diagram of measuring the photothermal temperature of the target material TANG-NDI COFs in Example 6 using an infrared camera.

[0034] In the figure: (a) is the initial image of the sample without illumination, (b) is the temperature measurement image taken by the infrared camera after illumination for 60 seconds, and (c) is the temperature measurement image taken by the infrared camera after illumination for 100 seconds.

[0035] Figure 8 This is the cyclic catalytic yield diagram of the target material TANG-NDI COFs in Example 8. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with the embodiments.

[0037] Example 1

[0038] The preparation of the target material comprises the following steps:

[0039] Step 1, dissolve a mixture of 2,6-difluoroaniline (26 g, 0.20 mol), 3-fluoro-2-iodoanisole (15 g, 0.06 mol), potassium carbonate (60 g, 0.43 mol), copper powder (15 g, 0.23 mol) and 18-crown-6 (5 g, 0.019 mol) in 160 ml of 1,2-dichlorobenzene, and cycle vacuum-nitrogen three times. Stir the mixture at 160 ° C for 17 hours, filter out insoluble matter through a Buchner funnel, concentrate the filtrate under reduced pressure, and purify it by silica gel column chromatography to obtain 12.60 g of light yellow powder;

[0040] Step 2: Add the light yellow powder (12.60 g, 0.050 mol) obtained in step 1 into a round-bottom flask, and add 2-iodo-1,3-dimethoxybenzene (40 g, 0.15 mol), 18-crown ether-6 (5 g, 0.019 mol), potassium carbonate (30 g, 0.21 mol), copper powder (10 g, 0.16 mol) and 170 ml of mesitylene, and stir the mixture at 210 °C for 50 hours. Filter the insoluble matter through a Buchner funnel, concentrate the filtrate under reduced pressure, and purify the crude product by silica gel column chromatography to obtain 15.6 g of white powder;

[0041] Step 3, the white powder (15.60 g, 0.040 mol) obtained in step 2 was added to a round-bottom flask, and 300 ml of dry CH2Cl2 was added, the system was cooled to -78 °C, 70 ml of BBr3 was added and slowly stirred for 9 hours to warm to room temperature, and then the reaction mixture was poured into ice water, extracted with ethyl acetate, and then filtered and concentrated under reduced pressure to obtain a demethylated crude product as a white solid. The white solid was dissolved in 220 ml of DMF, potassium carbonate (15 g, 0.10 mol) was added, and the mixture was stirred at 110 °C for 24 hours. The insoluble matter was filtered out through a Buchner funnel, and the filtrate was concentrated under reduced pressure. The crude product was purified by silica gel column chromatography to obtain 8.61 g of a light yellow powder;

[0042] Step 4: Slowly add the light yellow powder (8.61 g, 0.03 mol) obtained in step 3 into a round-bottom flask containing 60 ml 70% HNO3 and placed in an ice bath, then slowly add 13 ml (CH3CO)2O and 22 ml CH3CO2H, stir the mixture at constant temperature for 35 minutes, then pour the mixture into ice water, filter the precipitate to obtain 8.4 g of dark red powder;

[0043] Step 5: Add the dark red powder (8.4 g, 0.02 mol) obtained in step 4 into a round-bottom flask, and add 60 ml of dry tetrahydrofuran and 9 g of 10% Pd / C catalyst. Connect a hydrogen bottle to the outlet of the round-bottom flask, purge the mixture with hydrogen, and react at room temperature for 36 hours. Then, filter out the insoluble matter in a glove box, and evaporate the filtrate to dryness under reduced pressure to obtain 4.98 g of dark green powder, i.e., the organic ligand NH2-TANG.

[0044] Step 6. Weigh the organic ligand NH2-TANG (300 mg, 0.9 mmol) and naphthalene tetracarboxylic anhydride (362 mg, 1.4 mmol), add them into a heat-resistant glass tube containing 10 ml of m-cresol, 2 ml of methyl pyrrolidone and 0.1 ml of isoquinoline mixed solvent, and disperse them evenly by ultrasonication; freeze the glass tube with liquid nitrogen and seal the tube mouth with a flame under vacuum, then put it into an oven with a temperature control program, heat it to 200°C, and keep the constant temperature for 110 h; after the reaction is completed and cooled to room temperature, remove the supernatant, add m-cresol for washing, centrifuge, repeat the operation 3 times, collect the bottom product, and obtain 300 mg of black powder, i.e., the target material trioxytriphenylamine-based covalent organic framework TANG-NDI COFs. The powder PXRD pattern is as follows: Figure 3 As shown, after modeling and Pawley refinement, the crystal structure diagram is obtained, as shown Figure 1 As shown, the crystal structure belongs to the triclinic system, P-1 space group (a = 32.05Å, b = 32.18Å, c = 3.56Å, R wp =1.65%, R p =2.20%), its asymmetric structural unit is composed of three crystallographically independent naphthalene diimide NDI fragments and two triaminotrioxytriphenylamine ligands NH2-TANG. The material stacking mode is the classic AA stacking type, and the interlayer TANG-TANG and NDI-NDI have obvious π...π stacking effect.

[0045] The monomer was prepared by dissolving the organic ligand NH2-TANG (900 mg, 2.7 mmol) and 1,8-naphthalene dicarboxylic anhydride (1880 mg, 9.5 mmol) in 35 ml of m-cresol, reacting at 165 °C for 24 h, and then filtering to obtain 1.57 g of the monomer as a brown powder.

[0046] Example 2

[0047] 2 mg TANG-NDI COFs and 2 mg monomer were weighed and mixed with 200 mg KBr respectively, added into an agate mortar and ground into powder, then loaded into a tablet pressing metal mold and pressed using a tablet press. The two samples were then put into a Fourier transform infrared spectrometer for testing. The infrared spectra of the target material TANG-NDI COFs and monomer are shown in Figure 2. Figure 2 As shown in Figure 2, both of them showed typical cyclic imide stretching vibration peaks (1715 cm -1 、1675 cm -1 and 1708 cm -1 、1670 cm -1 ), which can demonstrate the successful synthesis of TANG-NDI COFs and monomers.

[0048] Example 3

[0049] Thermogravimetric analysis of the target material TANG-NDI COFs, such as Figure 4 As shown in the figure, the quality of TANG-NDI COFs decreases significantly in the range of 100-200°C because its BET specific surface area is large and it adsorbs more solvents such as m-cresol used in the firing process. In the temperature range of 450-500°C, the chemical bonds in the material begin to break and the structure is destroyed. The high stability of the material ensures that the catalyst can be recycled and reused many times.

[0050] Example 4

[0051] Weigh 5 mg of TANG-NDI COFs into an agate mortar and grind it into powder, then place it in the center of the groove of the quartz glass sheet, cover the groove with another quartz glass sheet, and adjust the positions of the two quartz glass sheets so that the powder is distributed as evenly as possible in the groove without gaps. The UV-visible absorption spectrum of TANG-NDI COFs is shown in Figure 1. Figure 5 As shown, it reflects the optical properties of TANG-NDI COFs. Compared with monomers, TANG-NDI COFs have a wider absorption range, especially 650nm ~ 900nm belongs to the charge transfer (DACT) absorption peak caused by DA between TANG and NDI. It is also because of the DACT effect that the material has the characteristics of near-infrared absorption, and the wider absorption band is conducive to the absorption of wide-spectrum light sources, improving the utilization efficiency of sunlight, thereby improving the catalytic efficiency of photothermal catalysis.

[0052] Example 5

[0053] Weigh 5 mg of TANG-NDI COFs into an agate mortar and grind it into powder in a glove box. Then put it at the bottom of the EPR tube and seal it with a rubber stopper. Perform electron paramagnetic resonance test at room temperature. The electron paramagnetic resonance spectra of the target material TANG-NDICOFs and the monomer are as follows: Figure 6 As shown, the EPR spectrum shows that the material has a strong electronic paramagnetic characteristic signal in the steady state, proving that the material has free radical characteristics. The strong DA effect causes a large degree of charge separation inside the molecule, which on the one hand leads to a red shift of the absorption peak, and on the other hand shortens the band gap of the material, which weakens the fluorescence of the material and enhances thermal relaxation. Most excitons return to the ground state through thermal relaxation, which greatly improves the photothermal conversion ability of the material. At the same time, the large specific surface area and porosity ensure sufficient contact between the material and the substrate molecules, further improving the photothermal catalytic efficiency.

[0054] Example 6

[0055] Weigh 20 mg of TANG-NDI COFs and place them on weighing paper. Use near-infrared LED lamp to continuously irradiate them in the glove box. Use infrared camera to perform dynamic temperature detection on one side. The schematic diagram of infrared camera measuring photothermal temperature of target material TANG-NDI COFs is shown in the figure. Figure 7 As shown, the material temperature rises to 88.1°C in 60 seconds and to over 130°C in 100 seconds. Since the infrared camera tests the average temperature of the material surface, the temperature of the material at a smaller molecular scale will be higher, which also ensures that the reaction barrier required for most organic reactions can be reached, which intuitively proves the photothermal conversion of the material.

[0056] Example 7

[0057] Add 4-chlorobenzonitrile (27.4 mg, 0.2 mmol), 4-fluorophenylboric acid (28 mg, 0.2 mmol), potassium phosphate (64 mg, 0.3 mmol), 8 mol% tetrakis(triphenylphosphine)palladium (18.48 mg, 0.016 mmol), 5% TANG-NDI COFs (8 mg, 0.01 mmol) to a dry photoreaction tube and add them to 1 ml of dioxane. The different reaction conditions are shown in Table 1. The reaction system is treated with nitrogen bubbling to remove oxygen in the solid system, and irradiated with a near-infrared LED. The reaction is carried out at room temperature (rt) for 24 h, and the catalyst is separated by an organic filter membrane. The filtrate is dried by rotary evaporation, and the crude product is separated by thin layer chromatography. The substrate expansion of the Suzuki reaction catalyzed by TANG-NDICOFs is shown in Table 2.

[0058] Table 1

[0059]

[0060] Table 2

[0061]

[0062] Example 8

[0063] The target material collected after the reaction is filtered and recovered, washed with an organic solvent and then put back into the target reaction for catalysis. The yield is calculated after the product is collected. The cyclic catalytic yield diagram of the target material TANG-NDI COFs is shown in Figure 8 As shown, after 5 cycles, the catalytic effect of the catalyst is still significant, which indicates that the framework structure is not destroyed during the reaction, proving the cyclic stability of the material, that is, the target material can be well recycled and reused.

Claims

1. A method for preparing a trioxytriphenylamine-based covalent organic framework having near-infrared photothermal catalytic Suzuki reaction performance, characterized in that: Using triaminotrioxytriphenylamine NH2-TANG as an organic ligand and naphthalene diimide NDI as a linking group, a trioxytriphenylamine-based covalent organic framework TANG-NDI COFs with near-infrared photothermal catalytic Suzuki reaction performance was prepared by a solvothermal method. The synthesis route is as follows: NH2-TANG +NDI→ TANG-NDI COFs; The organic ligand NH2-TANG has the following molecular structure formula (A): ; The connecting group has the following molecular structure formula (B): ; In order to verify the structure of the material later, the corresponding monomer was synthesized with the following molecular structure formula (C): ; The preparation method includes the preparation of the target material and the preparation of the monomer, wherein the preparation of the target material includes the following steps: Step 1, dissolving a mixture of 25-35 g 2,6-difluoroaniline, 12-21 g 3-fluoro-2-iodoanisole, 52-70 g potassium carbonate, 12-20 g copper powder and 3.2-6 g 18-crown ether-6 in 120-200 ml 1,2-dichlorobenzene, subjecting the mixture to 2-3 vacuum-nitrogen cycles, stirring the mixture at 120-160 ° C for 12-18 hours, filtering out insoluble matter through a Buchner funnel, concentrating the filtrate under reduced pressure, and purifying by silica gel column chromatography to obtain a light yellow powder; Step 2, adding the light yellow powder obtained in step 1 to a round-bottom flask, and adding 35-45 g of 2-iodo-1,3-dimethoxybenzene, 2-5 g of 18-crown ether-6, 30-50 g of potassium carbonate, 9-15 g of copper powder and 150-200 ml of mesitylene, and then stirring the mixture at 160-210 ° C for 40-56 hours, filtering out insoluble matter through a Buchner funnel, concentrating the filtrate under reduced pressure, and purifying the crude product by silica gel column chromatography to obtain a white powder; Step 3, add the white powder obtained in step 2 to a round-bottom flask, and add 300-350 ml of dry CH2Cl2, cool the system to -78 °C, add 65-80 ml of BBr3 and slowly stir for 6-12 hours to warm to room temperature, then pour the reaction mixture into ice water, extract with ethyl acetate, filter and concentrate under reduced pressure to obtain a demethylated crude product as a white solid, dissolve the white solid in 200-230 ml of DMF, add 15-25 g of potassium carbonate, and stir the mixture at 100-120 °C for 18-24 hours, filter out insoluble matter through a Buchner funnel, concentrate the filtrate under reduced pressure, and purify the crude product by silica gel column chromatography to obtain a light yellow powder; Step 4: Slowly add the light yellow powder obtained in step 3 into a round-bottom flask containing 50-75 ml 69-71% HNO3 and placed in an ice bath, then slowly add 12-15 ml (CH3CO)2O and 20-25 ml CH3CO2H, stir the mixture at a constant temperature for 25-45 minutes, then pour the mixture into ice water, filter the precipitate to obtain a dark red powder; Step 5, add the dark red powder obtained in step 4 to a round-bottom flask, and add 40-65 ml of dry tetrahydrofuran and 8-10 g of 10% Pd / C catalyst, connect a hydrogen bottle to the outlet of the round-bottom flask, purge the mixture with hydrogen, and react at room temperature for 24-36 hours, then filter out the insoluble matter in a glove box, and evaporate the filtrate to dryness under reduced pressure to obtain a dark green powder, i.e., the organic ligand NH2-TANG; Step 6, weighing the organic ligand NH2-TANG and NDI in a molar ratio of 1:1.2~1.5, adding them to a heat-resistant glass tube containing a mixed solvent of m-cresol, methyl pyrrolidone, and isoquinoline in a volume ratio of 1:0.2~0.3:0.005~0.012, and ultrasonically dispersing them uniformly; using liquid nitrogen to freeze the glass tube and flame-seal the tube mouth under vacuum, then placing it in an oven with a temperature control program, heating it to 180~200°C, and maintaining a constant temperature reaction for 100~120h; after the reaction is completed and cooled to room temperature, removing the supernatant, adding m-cresol for washing, centrifuging, repeating the operation 2~3 times, collecting the bottom product, and obtaining a black powder, i.e., the target material trioxytriphenylamine-based covalent organic framework TANG-NDI COFs; The monomer is prepared by dissolving the organic ligand NH2-TANG and 1,8-naphthalene dicarboxylic anhydride in 35-60 ml of m-cresol at a molar ratio of 1:3-5, reacting at 160-200 °C for 24-36 hours, and then filtering to obtain the monomer as a brown powder.

2. Use of trioxytriphenylamine-based covalent organic framework TANG-NDI COFs prepared by the method according to claim 1 in near-infrared photothermal catalysis Suzuki reaction.